2012
DOI: 10.1158/1078-0432.ccr-11-1973
|View full text |Cite
|
Sign up to set email alerts
|

Iniparib Nonselectively Modifies Cysteine-Containing Proteins in Tumor Cells and Is Not a Bona Fide PARP Inhibitor

Abstract: Purpose: PARP inhibitors are being developed as therapeutic agents for cancer. More than six compounds have entered clinical trials. The majority of these compounds are b-nicotinamide adenine dinucleotide (NAD þ )-competitive inhibitors. One exception is iniparib, which has been proposed to be a noncompetitive PARP inhibitor. In this study, we compare the biologic activities of two different structural classes of NAD þ -competitive compounds with iniparib and its C-nitroso metabolite.Experimental Design: Two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 42 publications
4
94
1
Order By: Relevance
“…Our findings suggest that response to both olaparib and iniparib is variable from cell line to cell line and independent of molecular subtype. Despite this variability, and in agreement with recent reports, 20,21 we found that olaparib was a more potent inhibitor of cell growth than iniparib in almost all the cell lines investigated. Our results are thus consistent with recent studies showing that iniparib was a weak inhibitor of PARP1.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings suggest that response to both olaparib and iniparib is variable from cell line to cell line and independent of molecular subtype. Despite this variability, and in agreement with recent reports, 20,21 we found that olaparib was a more potent inhibitor of cell growth than iniparib in almost all the cell lines investigated. Our results are thus consistent with recent studies showing that iniparib was a weak inhibitor of PARP1.…”
Section: Discussionsupporting
confidence: 93%
“…However, these results could not be reproduced in a phase III trial, raising questions about the future of PARP inhibition as a therapeutic strategy. Remarkably, in striking analogy with tivantinib, subsequent studies showed that iniparib is not a PARP inhibitor but a cytotoxic agent that kills tumor cells by an unrelated molecular mechanism (37,38). In the iniparib as in the tivantinib case, more rigorous preclinical analysis would have addressed these drugs toward a more appropriate clinical testing, preventing failure, and misinterpretation of clinical trials (39).…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, the interim analysis of the SOLTINeoPARP trial, a randomized phase II study that examined the efficacy of iniparib addition to weekly paclitaxel in the neoadjuvant setting of TNBC, failed to meet its primary endpoint that was pCR improvement [68] . Newer in vitro data though recognized that iniparib is not a selective PARP inhibitor [69,70] and its antineoplastic action could be attributed to the modification of cystein-containing proteins [69] , explaining its failure in the TNBC population. Other selective third generation PARP inhibitors, namely olaparib and veliparib, could be more effective and are investigated in clinical trials.…”
Section: Novel Agents In the Neoadjuvant Treatment Of Tnbcmentioning
confidence: 99%